Synergy effects in learning? The influence of mathematics as a second subject on teacher students' physics content knowledge. Issue 10 (3rd October 2021) - Neumann, Irene; Sorge, Stefan; Hoth, Jessica; Lindmeier, Anke; Neumann, Knut; Heinze, Aiso
ABSTRACT: This study explores benefits of studying two related subjects, mathematics and physics, in teacher education. German teacher students study two subjects as a major, which allows for investigating how the development of content knowledge in one subject, mathematics, benefits students' content knowledge in the other subject, physics. The sample included teacher students from 12 major teacher education universities in Germany. Each of the N = 104 physics teacher students, whose second subject was mathematics, answered two tests assessing their content knowledge in (1) mathematics and (2) physics. Our results reveal an influence of taking mathematics as a second subject on students' physics content knowledge. However, the effect size is only small. We found this influence increased over the course of study, indicating that the study of academic mathematics provided increasing opportunities to learn physics over the course of study. Even when controlling for general cognitive abilities, there remains substantial and significant effect of mathematics on physics content knowledge. Mathematical knowledge proves to be relevant in all physical subdomains except for optics and solid-state physics. Overall, the present study confirms benefits of studying physics when also studying mathematics, and thus a synergy effect in studying two subjects in scope of teacher education.